2016
DOI: 10.3164/jcbn.15-104
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil myeloperoxidase and its substrates: formation of specific markers and reactive compounds during inflammation

Abstract: Myeloperoxidase is an inflammatory enzyme that generates reactive hypochlorous acid in the presence of hydrogen peroxide and chloride ion. However, this enzyme also uses bromide ion or thiocyanate as a substrate to form hypobromous or hypothiocyanous acid, respectively. These species play important roles in host defense against the invasion of microorganisms. In contrast, these enzyme products modify biomolecules in hosts during excess inflammation, indicating that the action of myeloperoxidase is both benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 65 publications
2
46
0
Order By: Relevance
“…Previous report suggests that MPO level promotes oxidative stress through the production of hypochlorous acid and is found elevated in patients with active RA . Also, MPO is highly expressed in neutrophils . Therefore, the presence of elevated MPO activity in CIA mice and significant attenuation with F018 correlated well with the anti‐inflammatory effect of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Previous report suggests that MPO level promotes oxidative stress through the production of hypochlorous acid and is found elevated in patients with active RA . Also, MPO is highly expressed in neutrophils . Therefore, the presence of elevated MPO activity in CIA mice and significant attenuation with F018 correlated well with the anti‐inflammatory effect of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is a widely studied enzyme in the fields of inflammation as well as oxidative stress and is often used as a biomarker for many diseases including atherosclerosis, rheumatoid arthritis, and neurodegenerative diseases [21]. The most common diseases linked with the MPO system are summarized in Table 2 and include the changes of the MPO concentration or activity, the investigated matrix, and finally the method by which the MPO amount and/or its activity was determined.…”
Section: In Vivo Generation Of Hocl By the Mpo-h2o2 Systemmentioning
confidence: 99%
“…This is surprising, because Br − is about three orders of magnitude less abundant in comparison to Cl − (about 10 −1 versus 10 −4  M) and implies that bromide is preferentially metabolized by MPO. Furthermore, HOBr can be generated indirectly by the reaction between HOCl and bromide [39] which is also used to synthesize HOBr in the laboratory:T1Br+HOClHOBr+ClBoth HOCl and HOBr are strongly oxidizing agents with the ability to modify amino moieties in proteins, DNA or PLs (such as PE and PS) resulting in the generation of chloramines and bromamines as primary products [21]. …”
Section: In Vivo Generation Of Hocl By the Mpo-h2o2 Systemmentioning
confidence: 99%
“…This enzyme performs an essential function by carrying out antimicrobial activity using HOCl to invade the bacterial pathogens (Tian, Ding, Peng, & Lu, ). However, excessive HOCl may oxidize host biomolecules during inflammation, inducing necrosis in the surrounding tissue through oxidative stress mediated by the release of large amounts of reactive oxygen species (ROS) and HOCl (Kato, ). In this sense, Miric et al.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme performs an essential function by carrying out antimicrobial activity using HOCl to invade the bacterial pathogens (Tian, Ding, Peng, & Lu, 2017). However, excessive HOCl may oxidize host biomolecules during inflammation, inducing necrosis in the surrounding tissue through oxidative stress mediated by the release of large amounts of reactive oxygen species (ROS) and HOCl (Kato, 2016). In this sense, Miric et al (2010) demonstrated that upregulation of cerebral MPO activity, through ROS generation, was associated with intense inflammatory and oxidative damage, contributing to BBB disruption and bacterial invasion of the CNS.…”
mentioning
confidence: 99%